Vulnerability Assessment of Squatter Settlement in Butwal Sub-Metropolitan City, Nepal - Marasini, Manoj; Chidi, Chhabi Lal (The Third Pole: Journal of Geography Education, 2021)
Squatter settlement is uncontrolled and unplanned settlement consisting of dwelling built on land that is not owned. Squatters are the most vulnerable groups being very poor. This paper assessed the extent of socio-economic characteristics, causes of being squatters, vulnerability and their adaptation strategies of Sundarbazar area in Butwal. The descriptive analytical methodology was employed to generate data from both primary and secondary data sources. Out of 339 households, 113 households were selected through a systematic random sampling procedure. Field observation, focus group discussion and personal interviews were also applied to collect primary data. The squatter settlement in the study area has inadequate accommodation, poor access of safe water, sanitation, unmanaged waste disposal system and polluted environment. Poor economic condition, unemployment, and natural disaster along with availability of free land are the major cause of being squatters in this region. Furthermore, risk of health hazard, unemployment, and income uncertainty are the vulnerability of squatter people in the study area. It is concluded that poverty reduction in both rural and urban area can solve this problem but providing income generation opportunities, basic service facilities are major concern at present. In the developing countries like Nepal, squatter settlement is less known in literature and curriculum of formal education. Thus, it requires to aware new generation through school education system and the higher level for better urban planning and management in the future.